ANALISIS PENGARUH ANGKATAN KERJA, UPAH KARYAWAN DOMESTIK, DAN INFRASTRUKTUR TERHADAP PENANAMAN MODAL ASING DI JAWA TENGAH MELALUI BADAN PENANAMAN MODAL DAERAH (BPMD) PROVINSI JATENG (PERIODE 2000-2013) - Faisal Haris Pratama; Sri Marhaeni Salsiyah; Sri Wahyuni (Politeknik Negeri Semarang, 2015)
This study aims to identify and explain the impact of labor force, domestic labour wages, and infrastructure to foreign direct investment through BPMD Central Java. Data used in this study is secondary data and the analysis techniques used in this study is the technique of multiple linear regression analysis, F-test for simultaneously testing and t-test for partial testing. Results of data analysis showed simultaneously labor force, domestic labour wages, and infrastructure that had significant effect on foreign direct investment in Central Jawa. Ftest results show that the significant value 0.000<0.05 of significance level with a coefficient of determination (Adjusted R2) of 0.777, which means that the variable labor force, domestic labour wages, and infrastructure contribution amounting to 77,7%. The remaining 22,3% was explained by other variables. After the data were analyzed by SPSS 16 the equation of Y = 496926.173 + 0.377X1 + 0.135X2 - 21.5107X3 was founded. Partially, the labor force have positive and not significant impact to foreign direct investment in Central Java, the domestic labour wages have positive and significant impact to foreign direct investment in Central Java, and infrastructure have negative and significant impact to foreign direct investment in Central Java.